Comparing the Epidemiology and Health Burden of Lyme Disease and Babesiosis Hospitalizations in the United States. (8th November 2022) - Bloch, Evan M; Zhu, Xianming; Krause, Peter J; Patel, Eshan U; Grabowski, M Kate; Goel, Ruchika; Auwaerter, Paul G; Tobian, Aaron A R
Abstract: Background: Lyme disease (LD) and babesiosis are increasing in the United States. We sought to characterize and compare their epidemiology and health burden using a nationally representative sample of hospitalizations. Methods: Data were extracted from the National Inpatient Sample (NIS) pertaining to LD and babesiosis for 2018 and 2019. The NIS is a comprehensive database of all-payer inpatient hospitalizations, representing a stratified systematic random sample of discharges from US hospitals. Patient demographics, clinical outcomes, and admission costs were evaluated, in addition to hospital-level variables (eg, location/teaching status and census division). Annual incidence of hospitalizations was calculated using US Census Bureau data. Results: The annual incidence of hospitalizations of LD-related and babesiosis-related hospitalizations were 6.98 and 2.03 per 1 000 000 persons/year. Of the 4585 LD hospitalizations in 2018–2019, 60.9% were among male patients, 85.3% were White, and 39.0% were ≥60 years. Of the 1330 babesiosis hospitalizations in 2018–2019, 72.2% were among male patients, 78.9% were White, and 74.1% were ≥60 years; 70.0% of LD and 91.7% of babesiosis hospitalizations occurred in Middle Atlantic or New England. Lower disease severity was noted in 81.8% of LD hospitalizations compared with 49.3% of babesiosis hospitalizations, whereas those suffering from high severity were 2.3% and 6.0%, respectively. The mean hospital charges for LD and babesiosis hospitalizations were $33 440.8 and $40 689.8, respectively. Conclusions: Despite overlap between the 2 diseases, LD has a broader geographic range and a greater number of hospital admissions, whereas babesiosis is more severe, incurring longer hospital stays, higher inpatient costs, and deaths. Abstract : LD and babesiosis are major tickborne illnesses in the United States. In a large national database analysis, hospitalized babesiosis patients had a higher severity index, longer inpatient stays, and greater associated admission costs than hospitalized patients with LD.